2021
DOI: 10.3390/rs13234787
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Approaches to Monitoring the Spread of Invasive Species of Solidago spp.

Abstract: Global climate change influences plant invasion which spreads all over the Europe. Invasive plants are predominantly manifest negative impacts, which require increased attention not only from ecologists. The research examines the possibilities offered by geospatial technologies in mapping the spatial spread of invasive plants of the genus Solidago. Invasive plant population was investigated at two localities, Malý Šariš and Chminianska Nová Ves in Slovakia, as well as the mapping of the area by multispectral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…Our suggestion can provide understanding on the progressing increase of the number of ramets, as well as the clones of Canadian goldenrod, which were observed during the consecutive three years by the mapping of Solidago invaded plots with the help of various geospatial technologies. Moreover, the highest increase of both ramets and clones was observed just within the plots with the highest goldenrod % representation [33].…”
Section: Discussionmentioning
confidence: 86%
“…Our suggestion can provide understanding on the progressing increase of the number of ramets, as well as the clones of Canadian goldenrod, which were observed during the consecutive three years by the mapping of Solidago invaded plots with the help of various geospatial technologies. Moreover, the highest increase of both ramets and clones was observed just within the plots with the highest goldenrod % representation [33].…”
Section: Discussionmentioning
confidence: 86%
“…(Bolch et al., 2021) used a Trimble Geo7X RTK kit with a Zephyr‐3 antenna to record GNSS locations to conduct a differential correction using GPS Pathfinder Office to improve positional accuracies for monitoring aquatic plant invasions in the Sacramento‐San Joaquin River Delta, and Koco et al. (2021) surveyed Goldenrod‐invaded areas using a GNSS‐RTK GPS unit with an accuracy of <2 cm in Slovakia. If high accuracy GNSS is not available, upscaling the image GSD can help overcome positional errors (Gränzig et al., 2021).…”
Section: Results For Trends In Drone Remote Sensing Of Invasive Plantsmentioning
confidence: 99%
“…The use of post-processed kinematic (PPK) or real-time kinematic (RTK) global navigation satellite system (GNSS) can help capture the locational precision of GCPs needed to reference high spatial resolution drone imagery, and about 28% of studies reported using RTK-or PPK-GNSS for this purpose. Of note, Bolch et al (Bolch et al, 2021) used a Trimble Geo7X RTK kit with a Zephyr-3 antenna to record GNSS locations to conduct a differential correction using GPS Pathfinder Office to improve positional accuracies for monitoring aquatic plant invasions in the Sacramento-San Joaquin River Delta, and Koco et al (2021) surveyed Goldenrod-invaded areas using a GNSS-RTK GPS unit with an accuracy of <2 cm in Slovakia. If high accuracy GNSS is not available, upscaling the image GSD can help overcome positional errors (Gränzig et al, 2021).…”
Section: Photogrammetric Controlmentioning
confidence: 99%
“…15,16 In this regard, the use of remotely piloted aircraft systems (RPAS) for detecting invasive species in large and hard-to-reach areas has become more frequent, 7 driven by the development of sensors and positioning systems that enable the collection of high-resolution and accurate images at a low cost. 17 RPAS equipped with RGB, multispectral, and hyperspectral sensors play an essential role in the identification and monitoring of areas invaded by IAS, as reported in the studies by da Silva et al, 18 Koco et al, 19 Liang et al, 20 and Lopatin et al. 21 Furthermore, the processing of highresolution images obtained by RPAS can be handled by machine learning (ML) algorithms such as support vector machine (SVM) 22 and random forest (RF).…”
Section: Introductionmentioning
confidence: 99%
“…RPAS equipped with RGB, multispectral, and hyperspectral sensors play an essential role in the identification and monitoring of areas invaded by IAS, as reported in the studies by da Silva et al., 18 Koco et al., 19 Liang et al., 20 and Lopatin et al. 21 .…”
Section: Introductionmentioning
confidence: 99%